Collaborative lesson research: maximizing the impact of lesson study - Takahashi, Akihiko; McDougal, Thomas (ZDM, 2016)
New common standards for mathematics were adopted by most of the states in the US by 2010. Achieving these standards, however, is a challenge, since they require significant changes in how mathematics is taught. Lesson study ( jugyou kenkyuu ) is a form of professional development that has been credited for supporting profound changes in teaching in Japan, but its effectiveness outside of Japan has been uneven. From research on school-based lesson study in Japan and from the research on and experience with lesson study in schools in the US, the authors hypothesize that certain institutional structures and practices are important for maximizing its impact, but are sometimes omitted from lesson study outside of Japan. The authors introduce a new term: collaborative lesson research (CLR), defined to include those structures and practices. A three-phase model of school-based CLR, focused on implementation of the new learning standards for mathematics, is being piloted at 15 urban schools in three major school districts in the US. This paper provides details of the pilot program and preliminary results from some of the partner schools.